Evaluation of a new anaerobic power testing system - Hoffman, J. R.; Kang, J. (The Journal of Strength and Conditioning Research, 2002)
The purpose of this study was to evaluate the reliability of a new anaerobic athletic performance system. This system is proposed to assess vertical jump height, anaerobic power through repetitive jumping, and reaction to both an auditory and visual stimulus. One hundred twenty-three subjects (92 men and 31 women; mean ± SD: age, 20.5 ± 2.1 years; body weight, 83.1 ± 20.4 kg; height, 176.0 ± 9.2 cm) volunteered to participate. To assess reliability of the new testing device, subjects were tested on 3 separate occasions (T1, T2, and T3). At least 72 hours but not more than 1 week separated each laboratory visit. During each testing session subjects performed a countermovement jump (CMJ), a 30 consecutive jumps anaerobic power test (30JT), and reaction to both an auditory and visual stimulus. Results showed no differences between T1, T2, and T3 in either CMJ height or 30JT assessments. However, reaction to an audible or visual stimulus significantly improved during each testing session. Intraclass reliability of the CMJ and the 30JT was greater than 0.96 across the 3 trials. Pearson correlation coefficients of r > 0.90 were seen for the CMJ and 30JT, indicating a high test-retest reliability. The test-retest reliability for the reaction tests were lower (r ranging from 0.72 to 0.83). A Bland-Altman plot showed limited agreement between methods of vertical jump height assessment. Results indicate that this new testing device shows high reliability to assess both CMJ height and anaerobic power. In addition, anaerobic power assessment in a jump test provides a specific measure of anaerobic power for many sports incorporating similar performance patterns.